PLANT PARASITIC NEMATODES OF IMPORTANCE FOR SUGARCANE CROP IN BRAZIL - Rogerio de Carvalho, Tiago; Alexandre Cavichioli, Fabio; Dalvan do Nascimento, Daniel; Maria Soares, Nathalia (Revista Interface Tecnológica, 2023)
Sugarcane is of great importance for the production of sugar and ethanol, playing a crucial economic role in many countries, including Brazil. However, nematodes pose a significant threat to the crop, causing substantial yield and quality losses. This work aims to present the main nematodes that affect sugarcane crops, such as Meloidogyne spp. and Pratylenchus spp., examining their life cycles, visible symptoms of infestation and the damage caused to plants. Management strategies currently employed to control these nematodes are also presented, including crop rotation, use of resistant varieties, application of nematicides and improvement of soil management practices. Therefore, it can be concluded that nematodes cause serious economic losses in commercial areas, reinforcing the importance of research and development aiming to find more sustainable and effective solutions for management, such as genetic resistance of varieties and the use of bionematicides.